The contribution of public works programmes to poverty alleviation in Ward 14 of Bikita District, Zimbabwe. - Tandi, Costain (Midlands State University, 2017)
In the context of alarming poverty rates in rural Zimbabwe, this research was carried out to assess the contribution of public works programmes on poverty alleviation in ward 14 of Bikita district in Masvingo province. The research has been influenced by personal concerns which i strongly believe have influenced the selection of the research problem. My main concern is the deepening of poverty in the ward despite the prevalence of public works programmes as a policy option for the government to alleviate poverty. The main purpose of public works programmes is to make the unemployed more employable through the provision of temporary employment and training opportunities to the beneficiaries. Data collection took the form of unstructured interviews, observations, focus group discussions as well as document analysis. The nature of the enquiry was purely qualitative with narrative and content analysis used to explain the data. A small sample size of 25 respondents was selected using purposive sampling targeting the beneficiaries of public works programmes and those excluded in the programme but have no means of securing their basic needs. It is quite genuine to make a standing fact that the study findings indicated the positive impact of public works programmes on beneficiaries even though challenges were still enamours. The main conclusions are that any meaningful rural poverty alleviation strategy must be properly designed such that the government would go into partnership with rural people to make implementation easier, thus engendering economic self-sustenance, growth and development.